Antifungal acetylinic thiophenes from Tagetes minuta: potential biopesticide (Journal of Applied Botany and Food Quality, 2013)
Apart from thiophenes, which possess wide range of biocidal activity, aerial parts of Tagetes sp. contain essential oil. Oil components were reported to have antifungal activity, thus making whole plant of Tagetes very useful for exploiting as natural fungistatic agent. In the present study, Tagetes minuta grown in north western Himalayan condition were evaluated for its potential for use as antifungal agent. Flower essential oil showed minimal antifungal activity. Whereas, leaf essential oil was found signifi cant antifungal activity against three phytopathogenic fungi out of eight tested fungi. ED50 values were 165, 175 and 110 μg mL-1 against Rhizoctonia solani, Sclerotinia sclerotiorum and Sclerotium rolfsii, respectively. Thiophene rich extract of Tagetes minuta was found comparatively lesser active (ED50: 233-484 μg mL-1) than leaf essential oil against the same fungi. The present study shows that essential oil from leaves and thiophene rich extracts from marigold roots have signifi cantly good antifungal activity against a number of soil borne and foliar plant pathogens. The easy availability of these plants makes it an attractive potential candidate for development of natural fungicide.